Security Analysis of the VoIP (Voice Over Internet Protocol) System - wulan, alya; Rahman, Rakhmadi; Desvi (Etunas, 2023)
Voice over Internet Protocol (VoIP) is a communication technology that enables voice transmission over IP-based networks, offering advantages such as cost efficiency, flexibility, and service integration. Despite its benefits, VoIP faces significant security vulnerabilities due to its open architecture and dependence on public internet infrastructure. This study presents a literature-based analysis of the primary security threats targeting VoIP systems, including eavesdropping, Denial of Service (DoS) attacks, spoofing, session hijacking, and Network Address Translation (NAT) traversal problems. The research also discusses a range of countermeasures, including Secure Real-time Transport Protocol (SRTP), Transport Layer Security (TLS), Intrusion Detection and Prevention Systems (IDS/IPS), adaptive firewalls, and robust authentication protocols such as STIR/SHAKEN. While these technical solutions are effective, their success depends on proper implementation and continuous system monitoring. Although there may be minor trade-offs in performance, particularly in latency, such compromises are acceptable under global standards to ensure secure communication. The findings underscore the importance of a layered security strategy that maintains both protection and Quality of Service (QoS), making VoIP a dependable solution for critical sectors such as government, finance, and business.